Depression, anxiety and stress among students in Ho Chi Minh city - Kieu, Thi Thanh Tra (Đại học Quốc gia Hà Nội, 2020)
There are many different kinds of stressors in students ' life that may affect their physical and mental health . However , the evidences for mental or psychological problems , such as depression , anxiety and stress , among students in Ho Chi Minh city ( HCMC ) are limited.